Peran Da’I Kamtimbmas dalam Penanggulangan Geng Motor - Fadillah, Muna; Sahrul, Sahrul (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The role of a Da'i in Islam holds significant importance in the practice and propagation of the Islamic faith. A Da'i's primary responsibility is to impart teachings to all individuals, with the aim of upholding and preserving Islam, drawing from their own personal experiences in everyday life. The role of a Kamtibmas Da'i in dealing with motorbike gangs is also very important. From the results of an interview with Mr. Syukri who was appointed as the Medan Labuhan Kamtibmas Da'i. In responding to crimes that are rampantly committed by children today, the government and institutions related to children should take the following countermeasures: 1. Raid children who have the potential to become members of motorbike gangs, 2. Hold spiritual shower activities in mosques and mosques. at church every Thursday for children who have been caught by the Medan police, 3. Da'i Kamtibmas also holds outreach activities to the community to overcome motorbike gangs so that they do not develop further.